2015
DOI: 10.4168/aair.2015.7.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity Between the Soybean Protein P34 and Bovine Caseins

Abstract: PurposeSoy-based formulas are widely used as dairy substitutes to treat milk allergy patients. However, reactions to soy have been reported in a small proportion of patients with IgE-mediated milk allergies. The aim of this work was to explore whether P34, a mayor soybean allergen, is involved in this cross-reactivity.MethodsIn vitro recognition of P34 was evaluated by immunoblotting, competitive ELISA and basophil activation tests (BAT) using sera from allergic patients. In vivo cross-reactivity was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 38 publications
0
34
1
1
Order By: Relevance
“…21 This suggested some similarity in the IgE epitope sequence and a possible cross reaction of antibodies with two proteins of different species. 22,23 Preparation S did not show the presence of nonsoy proteins. A strong reaction with anti-β-glycinin antibodies (50% cross reactivity level) confirmed that β-glycinin is one of the main proteins in the S preparation ( Fig.…”
Section: Resultsmentioning
confidence: 86%
“…21 This suggested some similarity in the IgE epitope sequence and a possible cross reaction of antibodies with two proteins of different species. 22,23 Preparation S did not show the presence of nonsoy proteins. A strong reaction with anti-β-glycinin antibodies (50% cross reactivity level) confirmed that β-glycinin is one of the main proteins in the S preparation ( Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Nonetheless, it has been demonstrated that some patients are intolerant to such products, suggesting the cross‐reactivity between soy and cow milk proteins. It was reported that the α‐subunit of beta‐conglycinin (Gly m 5.0101) from the vicilin‐like protein family, the G4 subunit of glycinin (Gly m 6.0401) from legumin‐like proteins, and, more recently, the cysteine protease P34 (Gly m Bd30K) and the globulin P28 (Gly m Bd28K) are involved in cross‐reactivity phenomena with bovine caseins (Rozenfeld and others ; Katz and others ; Smaldini and others ; Curciarello and others ; Candreva and others ; Candreva and others ).…”
Section: Cross‐reactivity Of Milk Allergensmentioning
confidence: 99%
“…Curciarello et al. used overlapping 15‐mer peptides and mapped cross‐reactive B cell epitopes in the C‐terminal region .Noteworthy, in this study we have been able to map for the first time B cell epitopes in the entire molecule of Gly m 5.0101 using peptides in solution.…”
Section: Resultsmentioning
confidence: 66%
“…Fu et al also reported epitope 125-LRRHKNKNPFLFGSNRFE-142 as one of the major IgG-binding region of the Gly m 5.0101 using a pool of plasma from ten piglets [40]. Curciarello et al used overlapping 15-mer peptides and mapped cross-reactive B cell epitopes in the C-terminal region [14].Noteworthy, in this study we have been able to map for the first time B cell epitopes in the entire molecule of Gly m 5.0101 using peptides in solution.…”
Section: D5 Mab Identifies B Cell Epitopes In Recombinant Gly M 50101mentioning
confidence: 99%